PENGARUH UKURAN PERUSAHAAN, LEVERAGE, KEBIJAKAN DIVIDEN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Tiara Nur Oktaviani; Sutarmin Sutarmin (Fakultas Ekonomi Universitas 17 Agustus 1945 Cirebon, 2022)
Firm value is the investor's perception of the company which is often related to stock prices. A high stock price will make the value of the company also high. The purpose of this study is to determine the effect of firm size, leverage, dividend policy and profitability on firm value. The data for this study is sourced from the financial statements of consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2020 period. The population of this study were 52 companies and obtained 15 samples. The dependent variable in this study is firm value which is measured using Tobin's q. The independent variables in this study are firm size, leverage, dividend policy and profitability. The results of the study stated that firm size, leverage, dividend policy and profitability as measured by ROE had no effect on firm value, while the profitability variable measured by ROA had an effect on firm value.